Baptisan sebagai Penghapusan Hierarki: Kajian Eksegetis-Teologis atas Galatia 3:26-29 dan Tawaran Ulang Identitas Eklesial di tengah Masyarakat Majemuk - Valeria Sonata; Syani B. Rante Salu; Asih Rachmani Endang Sumiwi (STT Iman Jakarta, 2026)
This article examines Galatians 3:26–29 as a performative baptismal formula that functions to restructure the social identity of the early Christian community. Employing a grammatical-historical exegesis of the Greek text (NA28) alongside a socio-rhetorical analysis of the Galatian crisis, this study finds that the metaphor of